2013
DOI: 10.1364/oe.21.010393
|View full text |Cite
|
Sign up to set email alerts
|

Review of measures for light-source color rendition and considerations for a two-measure system for characterizing color rendition

Abstract: Twenty-two measures of color rendition have been reviewed and summarized. Each measure was computed for 401 illuminants comprising incandescent, light-emitting diode (LED) -phosphor, LED-mixed, fluorescent, high-intensity discharge (HID), and theoretical illuminants. A multidimensional scaling analysis (Matrix Stress = 0.0731, R(2) = 0.976) illustrates that the 22 measures cluster into three neighborhoods in a two-dimensional space, where the dimensions relate to color discrimination and color preference. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 23 publications
2
96
0
Order By: Relevance
“…As a bonus, this would also make it consistent with their interpretation of a second MDS analysis on CCT-renormalized metrics, whereby the second axis did not refer to 'preference' (see Figure 4 in Houser et al 51 ).…”
Section: Mds Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…As a bonus, this would also make it consistent with their interpretation of a second MDS analysis on CCT-renormalized metrics, whereby the second axis did not refer to 'preference' (see Figure 4 in Houser et al 51 ).…”
Section: Mds Analysissupporting
confidence: 68%
“…31,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] For an overview of past and recent work on colour rendition in general and a review of some of the other colour rendition metrics, the reader is referred to the literature. [50][51][52][53][54] A review of the work on memory and preferred colours in general can be found in Smet et al 55 …”
Section: Introductionmentioning
confidence: 99%
“…In 1967 Judd [56] proposed the Flattery index. In 1972 Thornton For comprehensive reviews about color rendering metrics, the reader may refer to [75,125].…”
Section: Indices For Assessing the Quality Of Lightmentioning
confidence: 99%
“…Therefore, describing the quality of a light source with only one metric is not sufficient [15][16][17][18] . To solve this problem, numerous efforts have been made 2-5, 10-14, 19, 20 .…”
Section: Introductionmentioning
confidence: 99%